Solid Waste Management in Island Communities: Case Study in Arjasa District, Kangean Island - Mahsuna Rahman Shabaria (EDP Sciences, 2021)
Arjasa is one of Districts located in Kangean Island Madura that has been densely populated by more than 86.000 people. However, the solid waste management system fulfilling the Government Regulation (PP) 81/2012 remains a challenge in the area. The local government has been struggling to provide adequate infrastructure due to their limited resources, let alone local communities’ participation in the waste management. Therefore, this study aims to determine a best-practice solid waste management system in the district. The assessment includes technical aspect (SNI 190394-1994), and in-depth survey on organizational concept and social participation. Waste sampling was done in 5 out of 19 villages in the district, i.e., Arjasa, Angon-angon, Kalisanka, Paseraman, and Pabian. The result shows that 35,282 ton/day of waste was generated in Arjasa District. The waste component was consisted of 62.70%, 15.17%, 10.10%, 0.27%, 1.03%, 0.47%, 0.37%, 1.27%, 0.37%, 1.5%, 0.37%, and 6.4% identified as compostable wastes (food wastes and garden wastes), plastics, papers/cardboards, wood, fabrics, cans, glass, rubber, e-waste, diapers, styrofoam, and residues, respectively. Based on its possible reduction and separation/processing method by the communities, the waste collection/transfer and transport system were then designed. The proper organizational structure involving the government and the communities was also determined.